Identification of multiple inter- and intra-genotype reassortment mammalian orthoreoviruses from Japanese black cattle in a beef cattle farm - Oba, Mami; Shimotori, Mayo; Teshima, Natsuko; Yokota, Tomoko; Takemae, Hitoshi; Sakaguchi, Shoichi; Mizuno, Shuntaro; Ishida, Hiroho; Murakami, Hironobu; Mizutani, Tetsuya; Nagai, Makoto (Scientific reports, 2024)
Mammalian orthoreoviruses (MRVs), belonging to the genus Orthoreovirus in the family Spinareoviridae , possess a double-stranded RNA segmented genome. Due to the segmented nature of their genome, MRVs are prone to gene reassortment, which allows for evolutionary diversification. Recently, a genotyping system for each MRV gene segment was proposed based on nucleotide differences. In the present study, MRVs were isolated from the fecal samples of Japanese Black cattle kept on a farm in Japan. Complete genome sequencing and analysis of 41 MRV isolates revealed that these MRVs shared almost identical sequences in the L1, L2, L3, S3, and S4 gene segments, while two different sequences were found in the S1, M1, M2, M3, and S2 gene segments. By plaque cloning, at least six genetic constellation patterns were identified, indicating the occurrence of multiple inter- (S1 and M2) and intra- (M1, M3, and S2) reassortment events. This paper represents the first report describing multiple reassortant MRVs on a single cattle farm. These MRV gene segments exhibited sequence similarity to those of MRVs isolated from cattle in the U.S. and China, rather than to MRVs previously isolated in Japan. Genotypes consisting solely of bovine MRVs were observed in the L1, M1, and M2 segments, suggesting that they might have evolved within the cattle population.